1996
DOI: 10.1111/j.1365-2133.1996.tb07949.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exchange therapy for solar urticaria

Abstract: We report two cases of severe idiopathic solar urticaria treated with plasma exchange therapy. Previous treatment which included antihistamines and, in one patient, desensitization with psoralens and ultraviolet A (PUVA) and narrowband ultraviolet B phototherapy produced only partial benefit. The effect of plasma exchange therapy was assessed using monochromator phototesting and intradermal injection of in vitro irradiated serum. One patient responded but relapsed within 2 weeks. We have failed to demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 15 publications
0
11
0
2
Order By: Relevance
“…[99][100][101] Combined treatment with plasmapheresis and psoralen plus UVA phototherapy (PUVA) in patients with circulating photoallergens has resulted in partial remission. 102 Mang et al 103 reported successful treatment of solar urticaria with extracorporeal photopheresis.…”
Section: Plasmapheresismentioning
confidence: 99%
“…[99][100][101] Combined treatment with plasmapheresis and psoralen plus UVA phototherapy (PUVA) in patients with circulating photoallergens has resulted in partial remission. 102 Mang et al 103 reported successful treatment of solar urticaria with extracorporeal photopheresis.…”
Section: Plasmapheresismentioning
confidence: 99%
“…UV-protective clothes for which compliance with the EN13758 is claimed must fulfill all stringent instructions of testing, classification, and marking, including a UPF >40 (UPF 40+), average UVA transmission <5%, and specific design requirements as specified in part 2 of Table IV. Therapeutics in immunologically mediated photodermatoses Therapy PLE [19,[50][51][52] Hydroa vacciniforme [2,28,50] Solar urticaria [38,51,[53][54][55][56][57] Actinic prurigo [2,24,51,58,59] Chronic actinic dermatitis [32,54,60,61] the standard. [62] Nevertheless, in patients with severe photosensitivity (e.g.…”
Section: Photoprotectionmentioning
confidence: 99%
“…azathioprine, mycophenolate mofetil, and calcineurin inhibitors, such as cyclosporine [ciclosporin] and tacrolimus) approaches are more frequently used in severe cases of actinic prurigo, solar urticaria, and or chronic actinic dermatitis. [48,[54][55][56][57][58][59][60][61]72,[75][76][77] …”
Section: Drug Therapymentioning
confidence: 99%
“…This modality has been reported to improve symptoms in the few patients included in these studies. One study failed to demonstrate a lasting benefit with plasmapheresis [92]. The effectiveness of this therapy may depend on the characteristics of the specific photoallergen at work (ie, circulating antigen versus cutaneous antigen).…”
Section: Treatmentmentioning
confidence: 99%